Comparison of the accuracy of apex locator, digital radiography, and cone-beam computed tomography in root canal working length determination in teeth with external root resorption: An in vitro study - Seyed Mohsen Hasheminia; Sanaz Jahadi; Farida Ghazanfari Moghaddam; Shervin Bagherieh (Wolters Kluwer Medknow Publications, 2024)
Background: The aim of this study was to compare the accuracy of apex locator, digital periapical radiography, and cone-beam computed tomography (CBCT) for determining the root canal working length (WL) in teeth with external root resorption (ERR). Materials and Methods: In this in vitro study, the sample consisted of 54 extracted permanent single-rooted human teeth. ERRs were performed at the 3 mm apical root using 65% of nitric acid for 24 h. After determining the actual WL by K-file #10 (gold standard) with the visualization method, the teeth were mounted in alginate and the WL of each tooth was determined using the electronic apex locator (EAL) equipped with a K-file #15. The teeth were mounted with wax in the teeth sockets of a dry human mandible, and the images were obtained by digital phosphor plate receptors and CBCT scans. The mean registered WL of each method was statistically compared with the gold standard WL using one-way ANOVA with P < 0.001. Results: The mean ± standard deviation (SD) of actual WL was 16.00 ± 2.24. The mean ± SD of WLs determined by CBCT, EAL, and digital radiography were 15.38 ± 2.19, 15.52 ± 2.32, and 16.83 ± 2.20, respectively. This study showed that the mean measured WL with ERR in all methods was significantly different from the actual WL (P < 0.001). Conclusion: This study showed that there was a significant difference between the actual mean WL and the EAL, digital periapical radiography, and CBCT mean WL. Thus, the combination of EAL and CBCT could be a reliable method for determining WL in the presence of ERR.